Principles of tissue engineering - Lanza, Robert.; Langer, Robert; Lanza, Robert; Vacanti, Joseph (Elsevier, 2014)
Now in its fourth edition, Principles of Tissue Engineering has been the definite resource in the field of tissue engineering for more than a decade. The fourth edition provides an update on this rapidly progressing field, combining the prerequisites for a general understanding of tissue growth and development, the tools and theoretical information needed to design tissues and organs, as well as a presentation by the world’s experts of what is currently known about each specific organ system. As in previous editions, this book creates a comprehensive work that strikes a balance among the diversity of subjects that are related to tissue engineering, including biology, chemistry, material science, and engineering, among others, while also emphasizing those research areas that are likely to be of clinical value in the future.